BIODISTRIBUTION STUDY OF 188Re-HEDP AS A RADIOPHARMACEUTICAL FOR BONE PAIN PALLIATION - Tripunoski, Toni; Mathe, Domokos; Balog, Lajos; Ugrinska, Ana; Chochevska, Maja; Stojanoski, Sinisa; Bozinovska, Nikolina; Manevska, Nevena; Jankulovska, Anamarija; Popgjorceva, Daniela (Journal of Morphological Sciences, 2023)
Bone seeking radiopharmaceuticals like Rhenium-188 hydroxy ethylidene diphosphonate ( 188 Re-HEDP) are used for palliative treatment of bone metastases, and as target radionuclide therapy in patients with inoperable osteosarcoma in addition to the external radiation therapy. In this study was evaluated the preparation, quality control and biodistribution of 188 Re-HEDP in mice to be determined the in vivo affinity to the target bone tissue and to the other non-target tissues and organs. 188 Re-HEDP was prepared with radiochemical purity of 98.87%. Its biodistribution data showed high uptake and durability in the skeletal tissues without significant uptake in other tissues and organs. It means that 188 Re-HEDP kit formulation and the prescribed conditions in our study allows obtaining a radiopharmaceutical with promising therapeutic efficiency in palliative treatment of primary bone tumors as well as secondary osseous metastatic lesions. Keywords: bone pain palliation, radionuclide therapy, radiopharmaceuticals, Rhenium-188